Gambling and negative life events in a nationally representative sample of UK men. (December 2017) - Roberts, Amanda; Sharman, Stephen; Coid, Jeremy; Murphy, Raegan; Bowden-Jones, Henrietta; Cowlishaw, Sean; Landon, Jason
Abstract: Introduction: The links between gambling problems, trauma and life stressors are known to exist but understanding the extent of these relationships will allow for greater efficacy in early intervention and treatment. We investigated these relationships among men and sought to determine whether links were attenuated by alcohol and drug use problems. Methods: A cross-sectional UK representative general population survey was conducted in 2009 with 3025 men aged 18–64 years. Measurements included self-reported gambling behaviours, as measured by the South Oaks Gambling Scale (SOGS) and traumatic or stressful life events. Covariates included alcohol and drug dependence and socio-demographics. Binary logistic regression models were used to examine associations. Results: Problem gambling (SOGS 3–4) and probable pathological gambling (SOGS 5 +) were associated with increased odds of trauma in childhood (e.g. violence in the home (Adjusted Odd Ratios (AOR) 3.0 (CI = 1.8–5.0) and 2.6 (CI = 1.7–4.1) respectively), and life stressors in adulthood (e.g. intimate partner violence (AORs 4.5 (CI = 2.0–10.3) and 4.7 (CI = 2.3–9.7) and homelessness (AORs 2.2 (CI = 1.1–4.6) and 3.2 (CI = 1.9–5.5)). Results were attenuated when adjusted for probable alcohol and drug dependence with the latter having largest effects. Conclusions: Among men in the United Kingdom, disordered gambling remains uniquely associated with trauma and life stressors in childhood and adulthood after adjusting for alcohol and drug dependence. The results support a need for disordered gambling treatment services to undertake routine screening for alcohol, drugs, IPV and traumatic life events and to tailor treatment that specifically targets the effects of stress for clients who present with such a cluster of issues. Highlights: Disordered gambling remains associated with trauma after adjusting for substance dependence. Disordered gambling is also linked to stressful life events. There are few rigorous studies that have demonstrated these links empirically.